COARCTATION OF AORTA IN A 21-YEAR-OLD FEMALE: A CASE REPORT. (June 2018) - Ouankou, C. Ngongang; Thiam, E. Many; Tsambang, L.; Ngamga, J. Wandji; Kapi, L.O. Chendjou; Tsamo, C.; Soule, I.L. Nchoua; Etoundi, A.; Tang, M.; Ouankou, M.D.
Abstract : Objective: It is a case report of a particular case of aorta coarctation associated to a superior vena cava duplicated on a 21 years old female. Figure. No caption available. Design and method: We describe a story of hypertension which lead to the diagnosis of aorta coarctation through cardiac ultrasound and confirm by angiography Results: Three months ago, she was addressed for a cardiologist consultation after a routine check-up during which was noted elevated blood pressure values. She presented with no relevant past history. Physical examination showed blood pressures of 182/89 mmHg (left arm) and of 194/89mmHg (right arm), a bradycardia of 52 beats/minute. On cardiovascular physical assessment was recorded a systolic murmur of intensity 4/6, posterior over the thoracic spine and sub clavicular. Femoral pulses were palpable bilaterally but weak and delayed compared to the brachial pulses. Her ambulatory blood pressure measurement (ABPM) showed a permanent systolic and paroxystic diastolic hypertension, with a daytime adrenergic component in a dipper. A regular sinus bradycardia on electrocardiographic examination with heart rate of 47 beats per minute. A mild enlarged cardiac silhouette without notching of the ribs were observed on the chest radiography. The echocardiogram showed……(see figure below). Thoracic computerised tomographic (CT) angiography showed an aortic isthmus coarctation with a rounded arch, the presence of a duplicated superior vena cava, dilatation of collateral partway below the coarctation to hypertrophied intercostal, internal mammary artery dilatation and Cardiomegaly with left ventricular dilatation; no lungs lesion. These findings are represented in figures below. Biological assessment done for renal function, glycaemia, lipid profile and blood uric acid level where normal. The patient was placed on Atenolol 50 mg and Nifedipine 20 mg daily then referred to cardiothoracic surgery for an angioplasty. Conclusions: Through this case, we presented a young female with an aortic coarctation fortuitously discovered during the evaluation of an asymptomatic hypertension. Prior to surgical management, Blood pressure controlled was achieved on pharmacological treatment. The particular aspect in this case was the association of a duplicated superior vena cava.